The Role of Shot Peening in Increasing X70 Steel Fatigue Properties - Mikova, Katarina; Guagliano, Mario; Bokuvka, Otakar; Trsko, Libor; Novy, Frantisek (Communications - Scientific letters of the University of Zilina, 2012)
The paper presents the authors’ results of experimental examination of pipeline steel X70 fatigue properties before and after shot peening application, including relaxation of residual stresses during rotating bendi ng fatigue loading (f 30 Hz, T 20 5 °C, R 1). The obtained results confirmed the positive effect of surface hardening realized by shot peening. The fatigue properties incl. fatigue limit were higher after shot peening and this effect was visibly higher for notched specimens than for smooth specimens. During rotating bending fatigue loading the residual stresses in subsurface layers relaxes which decreases the strengthening effect after a certain number of cycles.